The Foreigners in Postexilic Cultic Prescriptions of the Torah: between Constraint and Religious Freedom (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
This paper analyzes postexilic prescriptions of the Torah that refer to foreigners. It looks at whether regulations constrain or ensure the religious freedom granted to them. The law makes a distinction among several types of foreigners and is concerned mostly with resident aliens, whose religious freedom used to be conditioned. Some constraints were imposed by the majority, in an attempt to protect the development of its normal religious life (Ex 12:19; Lv 16:29). It was thought that the religious offence committed by the aliens might trigger negative outcomes for the Israelite community (Lv 20:2-5). Foreigners were not compelled to accept the religion of the majority Israelite community. In case they wanted to take part to the cultic life of the community, they were called to obey the same prescriptions as the Israelites (Ex 12:49; Nm 15:14-15). The integration of aliens in the Israelite cultic community was practically limited by the compulsoriness of circumcision (Ex 12:48).